Kikuchi-Fujimoto Disease: A Case Report and Literature Review - Vikrant Veer; Albert Lim; Wolfgang Issing (Case Reports in Otolaryngology)
Case. 38-year-old lady was referred to the ENT clinic with history of right-sided facial pain, otalgia, and odynophagia. Clinical examination revealed enlarged right-sided lymph nodes in the neck. Further radiological scans showed a mass near the carotid and enlarged level V lymph nodes. Lymphoma was initially suspected. Fine-needle aspiration and excision biopsy were undertaken. Histological analysis later suggested Kikuchi-Fujimoto disease, also known as histiocytic necrotising lymphadenitis. Literature Review. Kikuchi-Fujimoto disease (KFD) was described in 1972 as lymphadenitis with focal proliferation of reticular cells accompanied by numerous histiocytes and extensive nuclear debris. KFD, frequently found in East Asian countries, is rare in the UK. No definite aetiology of KFD is known despite autoimmune and infection factors being suggested. The diagnostic hallmark is histological findings from lymph nodes. Malignancy should be excluded. This condition is mainly self-limiting; hence, management is limited to supportive care. Steroid therapy could be used in severe cases. KFD is relatively unknown in the UK and this case report aims to highlight its occurrence in our population.